2013
DOI: 10.1038/mp.2013.67
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal neuronal differentiation and mitochondrial dysfunction in hair follicle-derived induced pluripotent stem cells of schizophrenia patients

Abstract: One of the prevailing hypotheses suggests schizophrenia as a neurodevelopmental disorder, involving dysfunction of dopaminergic and glutamatergic systems. Accumulating evidence suggests mitochondria as an additional pathological factor in schizophrenia. An attractive model to study processes related to neurodevelopment in schizophrenia is reprogramming of somatic cells into induced pluripotent stem cells (iPSCs) and differentiating them into different neuronal lineages. iPSCs from three schizophrenia patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
179
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(190 citation statements)
references
References 62 publications
9
179
0
Order By: Relevance
“…We have previously reported that a significant fraction of the gene signature of schizophrenia hiPSC-derived neurons is conserved in schizophrenia hiPSC-derived neural progenitor cells (NPCs), indicating that NPCs may be a useful cell type for studying the molecular pathways contributing to schizophrenia 1 . We and others have reported aberrant migration, increased oxidative stress and reactive oxygen species, sensitivity to sub-threshold environmental stresses and impaired mitochondrial function in schizophrenia hiPSC NPCs 1,[4][5][6] , as well as decreased neuronal connectivity and synaptic function in schizophrenia hiPSC neurons 5,[7][8][9][10] . If the molecular factors contributing to aberrant migration and/or oxidative stress in schizophrenia hiPSC NPCs also underlie the reduced neuronal connectivity in schizophrenia hiPSC-derived neurons, NPCs could be a robust and highly replicative neural population with which to study the mechanisms responsible for disease.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that a significant fraction of the gene signature of schizophrenia hiPSC-derived neurons is conserved in schizophrenia hiPSC-derived neural progenitor cells (NPCs), indicating that NPCs may be a useful cell type for studying the molecular pathways contributing to schizophrenia 1 . We and others have reported aberrant migration, increased oxidative stress and reactive oxygen species, sensitivity to sub-threshold environmental stresses and impaired mitochondrial function in schizophrenia hiPSC NPCs 1,[4][5][6] , as well as decreased neuronal connectivity and synaptic function in schizophrenia hiPSC neurons 5,[7][8][9][10] . If the molecular factors contributing to aberrant migration and/or oxidative stress in schizophrenia hiPSC NPCs also underlie the reduced neuronal connectivity in schizophrenia hiPSC-derived neurons, NPCs could be a robust and highly replicative neural population with which to study the mechanisms responsible for disease.…”
Section: Introductionmentioning
confidence: 99%
“…In accordance, a reduction in voltage-activated sodium and potassium currents, which may be linked to deregulated calcium homeostasis, has been observed in ALS iPSC-derived motor neurons [107]. from patients with schizophrenia and demonstrated that dopaminergic neurons failed to differentiate, whereas glutamatergic cells were not able to fully mature [110]. Impaired mitochondrial respiration was observed in both neuronal types as well as dissipation of mitochondrial membrane potential and disturbances in mitochondrial network structure.…”
Section: Mitochondrial Impairment In Ipsc Models Of Brain Disordersmentioning
confidence: 56%
“…However, accumulating evidence suggests mitochondria as an additional pathological factor in schizophrenia. Mitochondrial dysfunction and a disturbance in energy metabolism have been observed in schizophrenia patients and, likewise, mitochondrial disorders may present with psychotic, affective and cognitive symptoms (Manji et al, 2012;Robicsek et al, 2013). Recent data revealed that nuclear genes encoding mitochondrially localised proteins are over-represented among large, rare copy-number variations in schizophrenia patients, lending credence to the mitochondrial dysfunction hypothesis (Szatkiewicz et al, 2014).…”
Section: Do Neurons Have a Mechanism To Sense Upcoming Energy Needs?mentioning
confidence: 98%